Spectrophotometric determination of carbon dioxide and sulphur dioxide in wines by flow injection - Atanassov, G.T. (2011)
Flow injection analysis (FIA) methods for the spectrophotometric determination of CO2 and SO2 in wines are described. The determination of CO2 is based on the colour change of a low capacity buffer (containing an acid-base indicator) due to the dissolved carbon dioxide. The determination of SO2 is based on the decoloration of malachite green by sulphur dioxide. Two FIA manifolds are presented; one for the determination of CO2 in sparkling wines and another for the simultaneous determination of CO2 and SO2 in table wines. The analytes are isolated inside the manifold from the sample matrix using gas-diffusion units. Regression equations (FIA versus reference methods) showed no statistical difference, at 95 % confidence level, between the two sets of results for both determinations; additionally, for the determination of CO2, recovery values between 93.5 % and 111 % were found. RSD lower than 4.5 % for SO2 and 2.4 % for the CO2 determination were found. The sampling rates achieved were: 30 h–1 for the uniparametric system and 40 h–1 for the biparametric system. The single determination manifold is applicable in the concentration ranges of 0.5 to 4 g L–1 of CO2, and the simultaneous determination manifold in the range of 0.25 to 3 g L–1 of CO2 and 0.05 to 0.3 g L–1 of SO2